Prefrontal/accumbal catecholamine system processes high motivational salience - Puglisi-Allegra, Stefano; Ventura, Rossella (Frontiers in Behavioral Neuroscience, 2012)
Motivational salience regulates the strength of goal seeking, the amount of risk taken, and the energy invested from mild to extreme. Highly motivational experiences promote highly persistent memories. Although this phenomenon is adaptive in normal conditions, experiences with extremely high levels of motivational salience can promote development of memories that can be re-experienced intrusively for long time resulting in maladaptive outcomes. Neural mechanisms mediating motivational salience attribution are, therefore, very important for individual and species survival and for well-being. However, these neural mechanisms could be implicated in attribution of abnormal motivational salience to different stimuli leading to maladaptive compulsive seeking or avoidance. We have offered the first evidence that prefrontal cortical norepinephrine transmission is a necessary condition for motivational salience attribution to highly salient stimuli, through modulation of dopamine in the nucleus accumbens, a brain area involved in all motivated behaviors. Moreover, we have shown that prefrontal-accumbal catecholamine system determines approach or avoidance responses to both reward- and aversion-related stimuli only when the salience of the unconditioned stimulus is high enough to induce sustained catecholamine activation, thus affirming that this system processes motivational salience attribution selectively to highly salient events.